2018
DOI: 10.1111/jgs.15438
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Interventions Reduce High‐Risk Medications for Delirium in Hospitalized Older Adults

Abstract: Delirium threatens the functional independence and cognitive capacity of patients. Medications, especially those with strong anticholinergic effects, have been implicated as a preventable cause of delirium. We evaluated the effect of multicomponent interventions aimed at reducing the use of 9 target medications in hospitalized older adults at risk of delirium. This continuous quality improvement program was undertaken at a tertiary care facility and 4 community hospitals in a hospital system. We included 21, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 32 publications
(57 reference statements)
1
29
1
Order By: Relevance
“…Although there is ample evidence that spaced education, when delivered in an online format, can increase knowledge, this review has confirmed that clinicians’ retention of new knowledge is much greater with spaced education than traditional learning formats, and this knowledge is retained well after the initial online learning encounter . Spaced education's capacity to increase knowledge and change behaviour is reflected in its integration into recent multicomponent clinical practice change interventions . Although the observed changes noted in these two multicomponent interventions are not directly attributed to spaced education, the evidence emerging from our systematic review suggests that spaced learning pedagogy is likely to be a valuable addition to CPD interventions designed to promote the adoption of new evidence and drive practice change, but this needs to be confirmed in adequately powered RCTs.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although there is ample evidence that spaced education, when delivered in an online format, can increase knowledge, this review has confirmed that clinicians’ retention of new knowledge is much greater with spaced education than traditional learning formats, and this knowledge is retained well after the initial online learning encounter . Spaced education's capacity to increase knowledge and change behaviour is reflected in its integration into recent multicomponent clinical practice change interventions . Although the observed changes noted in these two multicomponent interventions are not directly attributed to spaced education, the evidence emerging from our systematic review suggests that spaced learning pedagogy is likely to be a valuable addition to CPD interventions designed to promote the adoption of new evidence and drive practice change, but this needs to be confirmed in adequately powered RCTs.…”
Section: Discussionmentioning
confidence: 70%
“…51,61 Spaced education's capacity to increase knowledge and change behaviour is reflected in its integration into recent multicomponent clinical practice change interventions. 71,72 Although the observed changes noted in these two multicomponent interventions are not directly attributed to spaced education, the evidence emerging from our systematic review suggests that spaced learning pedagogy is likely to be a valuable addition to CPD interventions designed to promote the adoption of new evidence and drive practice change, but this needs to be confirmed in adequately powered RCTs.…”
Section: Discussionmentioning
confidence: 87%
“…Taken together, our results suggest that strategies for preventing potential delirium and falls based on the patient's risk factors during allo-HCT may warrant further investigation. 32,37,43 Delirium and fall have profound negative impacts on the function, survival, and quality of life for general medical, surgical, and cancer patients, [17][18][19][20][21][22] although their impact on older allo-HCT patients is unknown. We have demonstrated that transplant-related delirium or fall was associated with significantly increased NRM.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the identification of potentially modifiable risk factors suggests that all older patients should benefit from pretransplant geriatric assessment and targeted interventions such as a pharmacist-led medication review, 46,47 pre-habilitation, and peritransplant delirium and fall prevention strategies. 32,37,43,48,49 We summarize potential prevention and intervention strategies in supplemental Table 4. Finally, given the negative consequences of geriatric syndromes, focused geriatric interventions such as intensified neurocognitive, physical, and occupational rehabilitation should be strongly considered for patients who developed these complications peritransplant.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses provided a mini handbook on POD to patients and their caregivers who had been identified via screening to be at risk of POD. A pharmacist and a group of geriatricians defined a list of 15 medications (chlorpheniramine, diphenhydramine, hydroxyzine, amitriptyline, scopolamine, alprazolam, clonazepam, diazepam, etizolam, lorazepam, triazolam, zolpidem, pethidine, famotidine, and ranitidine) that were reported to potentially cause delirium based on a review of previous studies and the frequency of use of these medications [17, 18]. To make a list of inappropriate medications for the elderly, we used the medication list in our hospital (2012 SNUBH Inappropriate Medication for Elderly Criteria), which is based on the 2008 Screening Tool of Older People’s Prescriptions criteria and 2012 Beers criteria [19].…”
Section: Methodsmentioning
confidence: 99%